A label-free photoelectrochemical cocaine aptasensor based on an electropolymerized ruthenium-intercalator complex. (20th November 2016) - Haddache, Fatima; Le Goff, Alan; Spinelli, Nicolas; Gairola, Priyanka; Gorgy, Karine; Gondran, Chantal; Defrancq, Eric; Cosnier, Serge
Graphical abstract: Highlights: Electrodes were modified by an electrogenerated Ru(II) complex which demonstrates photosensitive properties and intercalating properties towards the stem-loop base pairing domain of cocaine aptamers. Cocaine aptamers were immobilized as mono-and double-fragment which showed different behaviour towards photocurrent generation. The binding of aptamer could be followed by photelectrochemistry and modelized using a Langmuir-Freundlich isotherm. Using the double-fragment aptamer, a label-free photoelectrochemical aptasensor was designed, exhibiting a LOD of 10 nmol L −1 and linear range of 1 10 −8 –5 10 −4 mol L −1 . Abstract: A photoelectrode was designed by electrodeposition of a pyrrole monomer modified with a polypyridyl Ru(II) complex bearing benzo[i]dipyrido-[3, 2-a:2′.3′-c]phenazine (dppn) ligand. Owing to the intercalating properties of these immobilized complexes towards DNA double helix, cocaine aptamer was immobilized on the modified electrodes thanks to its stem-loop configuration in order to design a photoelectrochemical cocaine aptasensor. Especially using a double-fragment aptamer strategy, the binding of cocaine and the formation of the aptamer/cocaine complex was successfully observed and modeled by a Langmuir-Freundlich isotherm, giving access to an apparent dissociation constant Kd of 3.8 mmol L −1 . The photoelectrochemical aptasensor exhibits a LOD of 10 nmol L −1 and linear range of 1 10 −8 –5 10 −4 mol L −1 .